Asuhan gizi pada penderita hipertensi di layanan primer: Literatur review - Syamsu, Rachmat Faisal; Abdullah, A. Adila Permata; Mubarok, Rizqi; Nurdin, Abbas Zavey; Dahlia, Dahlia; Nasruddin, Hermiaty (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Hypertension is one of the most common chronic medical conditions characterized by persistently elevated arterial pressure. Hypertension has been one of the most studied topics in the past century and has become a significant comorbidity contributing to the development of stroke, myocardial infarction, heart failure, and kidney failure. Purpose: To determine nutritional care for patients with hypertension in primary care. Method: This literature review was conducted by searching, summarizing, and drawing conclusions from various previous studies. The search was limited to the period 2020 to 2025 using databases such as Sinta. The literature obtained was searched using the keywords